THE DEVELOPMENT OF LEGISLATION IN RELATION TO THE COST - MABUZA, PROMETHEUS S (My University, 2011)
Costing legislation basically means the process of determining the financial implications of developing and implementing legislation. There is widespread recognition of costing legislation as a budgeting and implementation planning tool however its role in promoting the ethos of good governance has not been fully examined in South Africa. Costing legislation has been undertaken without any guidelines, procedures or instructions on the importance of consulting with stakeholders. When guidelines or procedures are not spelt out and where consultation is not made a condition of the costing assignment then the door is left open for uncertainty. The purpose of this research study is to examine with the advantage of hindsight the two costing projects on the Child Justice Bill and Children’s Bill with a view to identifying good practice in terms of good governance standards that could be used to inform future costing projects. The study also seeks to find out whether costing as a process has within it any values which enhance good governance. In order to manage the study only three standards or indicators of good governance were examined and these were participation, accountability and transparency. The research findings were positive in spite of the fact that no guidelines for involving stakeholders had been suggested to the consultant in the two costing projects used as case studies. The research revealed that costing by its nature has to subscribe to the ethos of good governance in terms of participation, accountability and transparency. Costing utilises public funds thus the reason for requiring accountability and transparency. The research further revealed that whilst the costing projects examined were very consultative and complied with the three standards of good governance within government structures this did not extend to proper consultation with civil society and children. There are two recommendations that this research makes: consulting guidelines for costing of legislation must be developed and that the three standards examined iii must be used as the minimum standards for any costing process. Once guidelines have been developed it will bring increased certainty to all interested stakeholders because it will define more clearly the roles and responsibilities in the costing process.
MM - P&DM
Keywords: Legislation, Cost of; Implementation of legislation